2013
DOI: 10.1016/j.resuscitation.2013.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic post-conditioning and vasodilator therapy during standard cardiopulmonary resuscitation to reduce cardiac and brain injury after prolonged untreated ventricular fibrillation

Abstract: Aim of the study We investigated the effects of ischemic postconditioning (IPC) with and without cardioprotective vasodilatory therapy (CVT) at the initiation of cardiopulmonary resuscitation (CPR) on cardio-cerebral function and 48-hour survival. Methods Prospective randomized animal study. Following 15 minutes of ventricular fibrillation, 42 Yorkshire farm pigs weighing an average of 34±2 kg were randomized to receive standard CPR (SCPR, n=12), SCPR+IPC (n=10), SCPR+IPC+CVT (n=10), or SCPR+CVT (n=10). IPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Animal preparation has been described previously(6). See Supplement for full description of methods.…”
Section: Methodsmentioning
confidence: 99%
“…Animal preparation has been described previously(6). See Supplement for full description of methods.…”
Section: Methodsmentioning
confidence: 99%
“…20,21,26 Consequently, our recent results on the introduction of an ischaemic post conditioning protocol by limited interruptions of chest compressions during the first 3 min of CPR 5,6 were of a similar magnitude, with one important exception: neurologically intact survival after CPR, a decisive marker of resuscitation success, was significantly improved after prolonged untreated cardiac arrest, 5 indicating a considerable potential to improve cardiac and neurologic outcome and survival after a prolonged global ischaemic insult such as cardiac arrest by VF.…”
Section: Discusssionmentioning
confidence: 99%
“…We have recently shown that ischaemic post conditioning at the initiation of standard 5 or sodium nitroprusside-enhanced cardiopulmonary resuscitation (CPR) 6 significantly improved neurologically intact survival following 15 min of untreated ventricular fibrillation (VF) and concomitant global ischaemia in a porcine model of cardiac arrest. CPR was augmented by the use of an active compression/decompression (ACD) device 7 and an impedance threshold device (ITD).…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to restore myocardial and cerebral energy balance with improved perfusion, a series of studies [31,32 ■ ,3335] using a porcine model of ventricular fibrillation postulated that infusion of SNP during CPR would improve blood flow and perfusion of vital organs thereby improving resuscitation and recovery. Carotid blood flow, end-tidal CO 2 , and arterial pH were all increased with SNP treatment.…”
Section: Novel Therapiesmentioning
confidence: 99%